Transfer Factor of Heavy Metals from Sediments to Organs of Mud Crabs (Scylla serrata) of Mida-Creek, Kilifi Kenya - Ochieng, Emily Akinyi; Kayusi, Fredrick (CV. Literasi Indonesia, 2025)
Heavy metal accumulation and transfer from sediments to edible mud crab organs (Scylla serrata) pose major ecological and health risks to consumers. The bioaccumulation of these metals are detrimental if they are extremely toxic. The objectives of this study were to analyze heavy metal concentrations in sediments and crab organs and determine the transfer of heavy metals in Scylla serrata from sediments in Mida Creek, Kilifi. The crab samples were collected by simple random sampling whereas sediment samples were collected by purposive sampling. The transfer factor of heavy metals from sediments to the organs of edible mud crabs (Scylla serrata) was evaluated in both the wet and dry seasons. The measurements and examinations of heavy metals, samples of crab organs, and sediments were obtained from three sampled sites. The concentration of metals in the samples was determined using an X-ray fluorescence (XRF) spectrometer. The results showed that the majority of the components are accumulated by the crabs from sediments. The order in which the metal transfer factor to crabs from station 1 sediments increased was Fe > Zn > Ni > Cu > Cd > Hg. In station 2, the transfer factor increased in the following order: Fe > Zn> Cu>Ni>Cd> Hg, while in station 3, it increased in the following order: Fe > Ni> Zn>Hg>Cd>Cu. The study concluded that mud crabs in Mida Creek actively absorb most of the elements from the sediments. The study recommends a routine monitoring of heavy-metal levels in other crustacean marine biota, and fish is necessary.